2018
DOI: 10.33425/2639-8478.1019
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutations: A Possible Biomarker for Advanced Prostate Cancer

Abstract: Prostate cancer is an important type of cancer in males with the highest mortality rate after the lung cancer, especially in industrialized countries. RAS oncogenes, originating from proto-oncogenes with point mutations, play an important role in cancer cell proliferation. The RAS proto-oncogene mutations occur in 25% of human cancers. The aim of the study was to investigate the potential mutation of KRAS gene at exon 2 (codons 12/13), exon 3 (codon 61) and exon 4 (codon 117/146) in Turkish patients with prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Two studies have analyzed KRAS mutations in PCa in Turkey. Vural et al [41] reported a rate of 8.8%, similar to the current study. Besides, gene regions in which KRAS mutations occurred (exon 2, codon 12/13; exon 3, codon 61) were similar to our study.…”
Section: Discussionsupporting
confidence: 91%
“…Two studies have analyzed KRAS mutations in PCa in Turkey. Vural et al [41] reported a rate of 8.8%, similar to the current study. Besides, gene regions in which KRAS mutations occurred (exon 2, codon 12/13; exon 3, codon 61) were similar to our study.…”
Section: Discussionsupporting
confidence: 91%
“…More specifically, a decreased glycerophosphocholine (GPC) to phosphocholine (PC) ratio was reported in breast, ovarian, and prostate cancers [ 67 ], suggesting a tumor suppressor role for this gene in cancer. The NRAS gene is a well know oncogene in cancer that encodes for a GTP binding intracellular protein that interacts with the EGFR receptor and in 2018 has proposed as a possible biomarker for advanced prostate cancer [ 68 ].…”
Section: Discussionmentioning
confidence: 99%